The current status of neutrophil cytoplasmic antibodies - Woude, Fokko J. van der; Daha, Mohamed R.; Es, Leendert Adriaan van (Clinical & experimental immunology, 1989)
Several studies in the past 10 years have demonstrated the occurrence of autoantibodies against cytoplasmic constituents in patients with vasculitis and glomerulonephritis. In this review the nomenclature of these antibodies is discussed and assays and clinical associations are summarized. Although the antigens involved are not completely identified, antibodies and T cells reactive with myeloid lysozomal enzymes may both play a significant role in pathogenesis.